The electronic brain for intellectual systems and robots - Iashchenko, V.O. (Математичні машини і системи, 2016)
The technology of creation of the electronic brain for intellectual systems and androids is offered. Our solution of the problem of development of the electronic brain is the new architecture developed on the basis of a new type of the neural networks which do not have analog. On the basis of the multidimensional receptor-effector neural-like growing networks the theory and technology of development of systems with artificial intelligence is created. The technology is intended for creation of intellectual systems and robots of different function, and also for object management, having sensors and executive mechanisms. In the long term it is expected the receiving of full-fledged artificial intelligence. The purpose consists in realizing development of the artificial intelligence with new active, associative, uniform matrix structure for robots of various applications. It will allow creating robots assistants for the person which can understand the person and completely replace him in routine work or in dangerous places. The electronic brain can be used in any sphere of robotics, to be the virtual assistant in the normal computer or independent intellectual system. Пропонується технологія створення електронного мозку для інтелектуальних систем і андроїдів. Наше рішення проблеми розвитку електронного мозку – це нова архітектура, розроблена на основі нового типу нейронних мереж, які не мають аналога. На основі багатовимірних рецепторно-ефекторних нейроподібних зростаючих мереж створено теорію і технологію розробки систем зі штучним інтелектом. Технологія призначена для створення інтелектуальних систем і роботів різного призначення, а також для управління об'єктами, що мають датчики і виконавчі механізми. У перспективі – отримання повноцінного штучного інтелекту. Мета полягає в реалізації штучного інтелекту з новою активною, асоціативною, однорідною, матричною структурою. Це дозволить створити робота-помічника для людини, який може розуміти людину і повністю замінити його в повсякденній роботі або в небезпечних місцях. Електронний мозок може бути використаний у будь-якій сфері робототехніки, стати віртуальним помічником у звичайному комп'ютері або у незалежній інтелектуальній системі. Предлагается технология создания электронного мозга для интеллектуальных систем и андроидов. Наше решение проблемы развития электронного мозга – это новая архитектура, разработанная на основе нового типа нейронных сетей, которые не имеют аналога. На основе многомерных рецепторно-эффекторных нейроподобных растущих сетей созданы теория и технология разработки систем с искусственным интеллектом. Технология предназначена для создания интеллектуальных систем и роботов различного назначения, а также для управления объектами, имеющих датчики и исполнительные механизмы. В перспективе – получение полноценного искусственного интеллекта. Цель состоит в реализации искусственного интеллекта с новой активной, ассоциативной, однородной матричной структурой. Это позволит создать робота-помощника для человека, который может понимать человека и полностью заменить его в повседневной работе или в опасных местах. Электронный мозг может быть использован в любой сфере робототехники, стать виртуальным помощником в обычном компьютере или в независимой интеллектуальной системе.